Critical Analysis of Nutritional Factors in Disease Epidemiology and Prevention - Alyami , Askar Ali S; Hassan , Hassan Hebah T; Abaatahin , Saad Mohammed M Al; Al Amer , Hamad Mohammed H; Baaltahin , Saeed Ahmed M Al; Baalatahin , Mesfer Ahmed M Al; Alsallum , Abdullah Nasser M; Sulayyim , Mousa Abdullah M Al; Alsaleem , Dhaifallh Abdullah M; sulayyim , Habib Abdullah M Al; Al Salim, Nasser Ali A (Journal of Ecohumanism, 2024)
The burden of NCDs, including obesity, diabetes, CVDs, and some cancers, has upped the importance of nutrition in the health of a nation. Malnutrition and over nutrition, which are the major nutritional factors, play important roles in disease distribution in the world. With regard to the analysis of this paper, the author has given a critical perspective on how dietary habits, socioeconomic factors, and cultural practices are determinants of the epidemiology of diseases. Therefore, the present paper employs a literature review, epidemiological data, and case studies to unveil the connection between diet and disease as well as the way forward. Some of the discoveries made include understanding that poor diets are the leading causes of NCDs, micronutrient deficiencies are still a problem with the poor, and processed foods are very much a threat. The discussion reviews the difficulties in shifting to a healthier diet. It presents solutions for the economic issue and the behavioral modification problem in policy-making, healthcare approaches, and public health practice.